IMPLEMENTASI MODEL PEMBELAJARAN ADVANCE ORGANIZER MENGGUNAKAN ANIMASI DITINJAU DARI MINAT BELAJAR TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS VII PADA PELAJARAN IPA DI SMPN 1 BATUKLIANG TAHUN AJARAN 2014/2015 - Erlin Maryani; Muchlis -; Jamaluddin - (Postgraduate, University of Mataram, 2016)
This research was conclude in three main goals. Firstly, the effect of advance organizer implementation using animation on students natural science subject achievement VII Grade Students at SMP. Secondly, the effect of interest of students on learning on the advance organizer implementation using animation on students natural science subject achievement VII Grade Students at SMP. Lastly, the effect of combination between advance organizer implementation using animation and interest on students natural science subject achievement VII Grade Students at SMP. This research was a 2x2 factorial designs. The result of statistical analyzed using anava two ways showed at 5% level significant there were significant influence of advance organizer implementatoin using animation on students natural science subject achievement VII Grade Students at SMP (F count 396,6 > F table 6,81), interest of students on learning on the advance organizer implementation using animation on students natural science subject achievement VII Grade Students at SMP (F count 138,4 > F table 6,81), and the combination of between advance organizer implementation using animation and interest on students natural science subject achievement VII Grade Students at SMP (F count 61,95 > F table 6,81). This research was conclude that advance organizer implementation using animation, interest of students on learning on the advance organizer implementation using animation on students natural science subject, and combination of between advance organizer implementation using animation and interest on students natural science subject can highly influence of natural science learning achievements VII Grade Students at SMPN 1 Batukliang.Keyword: organizer, animation, interest, learning achievements.